2022
DOI: 10.1371/journal.pone.0271134
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable human resource management the mediating role between work engagement and teamwork performance

Abstract: The present work aims to analyze the properties of the working conditions recorded in the Sixth European Working Conditions Survey (EWCS); with it, it has being built seven independent indexes about different aspects of work’ quality in the health sector, and these constructs are used to evaluate their effects on work engagement (WE). In this sense, the originality of incorporating teamwork as a modulating variable is included. To analyze the effects of the job quality index (JQI) on the WE, a logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 105 publications
0
3
0
1
Order By: Relevance
“…Employees who are engaged often have a good attitude and are eager to cooperate with their coworkers. This cooperative atmosphere promotes successful collaboration, interaction, and information sharing, resulting in a peaceful workplace and increased collective job performance [87][88][89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees who are engaged often have a good attitude and are eager to cooperate with their coworkers. This cooperative atmosphere promotes successful collaboration, interaction, and information sharing, resulting in a peaceful workplace and increased collective job performance [87][88][89].…”
Section: Discussionmentioning
confidence: 99%
“…Engaged employees typically possess a positive attitude and a willingness to collaborate with their colleagues. This cooperative spirit fosters effective teamwork, communication, and knowledge sharing, leading to a harmonious work environment and improved collective job performance [87][88][89]. Additionally, studies by [90] have shown a positive correlation between work engagement and employee performance.…”
Section: The Relationship Between Work Engagement and Job Performancementioning
confidence: 99%
“…Team engagement emerges as a critical factor influencing overall team performance [ 20 , 21 ]. The engagement of a medical team has been shown to help reduce the stress of the work and improve professional performance and the quality of provided care [ 22 ]. Conversely, inadequate team engagement may result in adverse consequences, including diminished advice accuracy and comprehensiveness [ 23 ] and an increased likelihood of incorrect medical decisions [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Penelitian ini berupaya untuk meneliti kondisi kinerja pegawai non ASN sebagai wujud pengembangan kemampuan kerja tim yang dimediasikan oleh Kerjasama tim sebagaimana pendapat (Navajas-Romero et al, 2022). Perhatian peneltian pada pegawai non ASN disebabkan karena masih banyaknya pegawai non ASN yang belum diangkat menjadi Pegawai Pemerintah dengan Perjanjian Kerja (P3K) di kota Cilegon.…”
Section: Pendahuluanunclassified